Genetic variation at the IL10 gene locus is associated with severity of respiratory syncytial virus bronchiolitis. - Wilson, J; Rowlands, K; Rockett, K; Moore, C; Lockhart, E; Sharland, M; Kwiatkowski, D; Hull, J (2005)
The intense airway inflammatory response associated with respiratory syncytial virus (RSV) infection may be an important determinant in the severity of the disease. Interleukin (IL)-10 is a key regulatory cytokine known to be secreted during this infection. We investigated the role that IL-10 plays in RSV disease by studying the effects that variation in the IL10 gene has on the outcome of the disease. Eight single nucleotide polymorphisms (SNPs) spanning the IL10 gene were selected, and haplotypes were constructed. SNPs that efficiently tagged these haplotypes were then typed in 580 infants with severe RSV bronchiolitis and in 580 control subjects. None of the SNPs or haplotypes was associated with RSV bronchiolitis. In a subgroup analysis, 2 SNPs (IL10-1117 and IL10-3585) were associated (odds ratio, 1.7; P=.004) with the need for mechanical ventilation. These data are consistent with the theory that IL10 plays a role in the severity of RSV infection in infants.